Using Courts to Realize Education Rights : Reflections from India and Indonesia - Rosser, Andrew; Joshi, Anuradha (World Bank, Washington, DC, 2018)
This paper examines the role of courts in promoting fulfillment of the right to education in developing country democracies, focusing on India and Indonesia—two countries that have experienced increased education rights litigation in recent years. The paper argues that this litigation has been part of broader struggles over education policy, inequality, and the capture of educational institutions by political and bureaucratic forces; and that the extent to which litigation has been used and led to policy changes has depended significantly on the nature of, and access to, the court system; the presence of support structures for legal mobilization; the ideology of the courts and judges; and the roles and willingness of litigants to pursue redress. Broadly, litigation has served the interests of the poor and marginalized, although gains have largely come through better access to education, while issues of improving quality have been less prominent.